Expression and prognosis of CyclinA and CDK2 in patients with advanced cervical cancer after chemotherapy - Gao, Yongmei; Wang, Hui; Zhong, Aizhen; Yu, Tao (Cellular and Molecular Biology, 2020)
This study aimed to investigate the expression and prognosis of CyclinA and CDK2 in patients with advanced cervical cancer after chemotherapy. The patient history of 108 patients with advanced cervical cancer admitted to our hospital from December 2013 to January 2016 was selected as a cervical cancer group. 54 normal healthy people admitted to our hospital for physical examination in the same period were selected as the control group. Western blotting and RT-PCR were used to detect the difference between CyclinA and CDK2 proteins and mRNA expression between the two groups and the correlation between them was analyzed. The expressions of CyclinA and CDK2 in serum and the changes in detection index level of squamous cell carcinoma antigen (SCCA), carcinoembryonic antigen (CEA) and vascular endothelial growth factor (VEGF) were observed in cervical cancer group at different stages of treatment. The correlation between the two indexes and SCCA, CEA, VEGF and the 3-year survival and prognostic significance of cervical cancer patients with different CyclinA and CDK2 expressions were analyzed. The relative expressions of CyclinA and CDK2 proteins and mRNA in the cervical cancer group were significantly higher than those in the control group (P< 0.05). Pearson correlation analysis showed a positive correlation between CyclinA and CDK2 proteins and mRNA expressions. After treatment, the expressions of CyclinA, CDK2 mRNA and SCCA, CEA and VEGF were significantly lower than those before treatment (P< 0.05). The 3-year survival rate of CyclinA and CDK2 in the high expression group was significantly lower than that of the low expression group. CyclinA and CDK2 are highly expressed in advanced cervical cancer. The expression is decreased after chemotherapy. The prognosis of both low expressions is higher and the expression is good. It can be used to predict the efficacy and prognosis of cervical cancer in the clinic.